Structural and conformational analysis of SARS CoV 2 N-CTD revealing monomeric and dimeric active sites during the RNA-binding and stabilization: Insights towards potential inhibitors for N-CTD. (July 2021) - Chauhan, Arushi; Avti, Pramod; Shekhar, Nishant; Prajapat, Manisha; Sarma, Phulen; Bhattacharyya, Anusuya; Kumar, Subodh; Kaur, Hardeep; Prakash, Ajay; Medhi, Bikash
Abstract: The advent of SARS-CoV-2 has become a universal health issue with no appropriate cure available to date. The coronavirus nucleocapsid (N) protein combines viral genomic RNA into a ribonucleoprotein and protects the viral genome from the host's nucleases. Structurally, the N protein comprises two independent domains: the N-terminal domain (NTD) for RNA-binding and C-terminal domain (CTD) involved in RNA-binding, protein dimerization, and nucleocapsid stabilization. The present study explains the structural aspects associated with the involvement of nucleocapsid C-terminal domain in the subunit assembly that helps the RNA binding and further stabilizing the virus assembly by protecting RNA from the hosts exonucleases degradation. The molecular dynamics (MD) simulations of the N-CTD and RNA complex suggests two active sites (site I: a monomer) and (site II: a dimer) with structural stability (RMSD: 2 Å), Cα fluctuations (RMSF: 3 Å) and strong protein-ligand interactions were estimated through the SiteMap module of Schrodinger. Virtual screening of 2456 FDA-approved drugs using structure-based docking identified top two leads distinctively against Site-I (monomer): Ceftaroline fosamil (MM-GBSA = −47.12 kcal/mol) and Cefoperazone (−45.84 kcal/mol); and against Site-II (dimer): Boceprevir, (an antiviral protease inhibitor, −106.78 kcal/mol) and Ceftaroline fosamil (−99.55 kcal/mol). The DCCM and PCA of drugs Ceftaroline fosamil (PC1+PC2 = 71.9%) and Boceprevir (PC1 +PC2 = 61.6%) show significant correlated residue motions which suggests highly induced conformational changes in the N-CTD dimer. Therefore, we propose N-CTD as a druggable target with two active binding sites (monomer and dimer) involved in specific RNA binding and stability. The RNA binding site with Ceftaroline fosamil binding can prevent viral assembly and can act as an antiviral for coronavirus. Highlights: To understand the regulatory mechanism of protein-folding and RNA-binding at N-CTD, SARS CoV-2. Active sites proposed- Site-I (monomeric) & Site-II (dimeric) with interacting residues 258-330 & 264-320 respectively. The binding profile of the drugs were assessed by docking score, MD trajectory analysis, and ΔGbind . Top 2 leads binding at the monomeric site were Ceftaroline fosamil (-62.312 kcal/mol) and Cefoperazone (-52.421 kcal/mol). Boceprevir (-102.03 kcal/mol) and Ceftaroline fosamil (-106.16 kcal/mol) are the top compounds at dimeric site.